Dampak Konteks Politik Masa Intertestamental pada Penolakan Yesus Sebagai Mesias - Janes Pelealu (Sekolah Tinggi Teologi Berita Hidup, 2022)
If we want to understand the New Testament more deeply and broadly, it is not enough to interpret it from the text we read, but it is very important to understand the context behind the text. Because the New Testament is full of political, social, cultural, economic, geographical, biographical contexts, which are very different from our present context. It is highly recommended to study Intertestamental Theology, because the New Testament text is very closely related to the context of the Intertestamental period, indeed we cannot build theology from the Intertestamental period, but this period provides an important source of information for New Testament theology. For example, the theological questions that arise when we read the New Testament, are: Why did the Jews reject Jesus as the Messiah?, Why did the Sanhendrin reject Jesus? Even though they consist of groups of different sects and often clash, in terms of rejecting Jesus as the Messiah, they seem to be united in rejecting and agreeing to the decision of the Roman court to put Jesus to death. Of course the political context of the Intertestamental period will provide an answer. In relation to this question, it is important to discuss the topic: